The Effect of Using Edmodo Learning Media and Learning Motivation on Fiqih Learning Outcomes - Rahmah Fadilah Tanjung; Asnil Aidah Ritonga; Yahfizham Yahfizham (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
This study aims to find the effect of using Edmodo learning media on learning outcomes, the effect of learning motivation on learning outcomes, and the interaction between Edmodo learning media and learning motivation on Fiqh learning outcomes for students of class VIII MTsN 2 Medan. This type of research is a quantitative study with a population of all eighth-grade students consisting of 10 classes (401 students). Based on the Cluster Random Sampling technique, one class is used as a learning class with Edmodo media and another without Edmodo media. The research instruments used were tests and questionnaires. The normality test for learning outcomes data is the Liliefors test, and the homogeneity test is Fisher's and Bartlett’s tests. The data analysis technique used two-way ANOVA at significant = 0.05. The study’s results revealed an influence of Edmodo learning media on students' fiqh learning outcomes, where students' fiqh learning outcomes with Edmodo learning media were higher (26.22) than students' non-Edmodo learning media fiqh learning outcomes (23.25). The influence of learning motivation on learning outcomes obtained fiqh learning outcomes of students with high learning motivation was higher (27.12) than that of students with low learning motivation (22.03). While the interaction between learning media and learning motivation on students' fiqh learning outcomes through the results of the 2 x 2 ANOVA factorial calculation, the interaction factor value F = 9.113 and the P-Value = 0.004 smaller than 0.05. Thus there is an interaction between learning media and learning motivation on students' fiqh learning outcomes at MTsN 2 Medan.